2006
DOI: 10.1007/s00520-006-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the services provided by children’s hospices in the United Kingdom

Abstract: This study highlights that there is consistency in the high level of care being provided to children up to the age of 18, but provision of care after this age is patchy and not always readily available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…This was one more than was found by an earlier survey 15. Our survey did not ask about volunteer involvement specifically with older teenagers and young adults, so we do not know the extent of volunteering with this group.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This was one more than was found by an earlier survey 15. Our survey did not ask about volunteer involvement specifically with older teenagers and young adults, so we do not know the extent of volunteering with this group.…”
Section: Discussionmentioning
confidence: 80%
“…This was one more than was found by an earlier survey. 15 Our survey did not ask about volunteer involvement specifically with older teenagers and young adults, so we do not know the extent of volunteering with this group. However, young people prefer facilities separate from those for children 12 and can suffer significant social isolation.…”
Section: Young Peoplementioning
confidence: 99%
See 2 more Smart Citations
“…In 1967 the world's first modern hospice, St. Christopher's, opened in London (23). The first children's hospices were built 15 years later, and today there are about 40 in the United Kingdom (24). Pediatric palliative care has evolved over the past three decades, shifting from in-patient hospital and hospice care to home and community care, which studies have suggested could reduce costs and improve quality of life (25).…”
Section: United Kingdommentioning
confidence: 99%